Academic Supervision by School Principals: Enhancing Junior High School Teachers' Professional Competence - Julianda, Eka; Ismail, Ismail; Khairuddin, Khairuddin; Lala, Andi (Journal of Educational Management and Learning, 2024)
This study investigates the role of academic supervision by school principals in enhancing teacher professional competence at SMP Negeri 1 Babahrot and SMP Negeri 2 Susoh in Southwest Aceh, Indonesia. Employing a qualitative approach, the research examined the planning, implementation, and follow-up of academic supervision activities conducted by the school principals. The findings indicate that the principals' systematic approach to academic supervision includes comprehensive planning, active implementation, and targeted follow-up actions, all aimed at supporting the continuous professional development of teachers. The study demonstrates that these practices significantly improve teaching quality and student learning outcomes. Challenges such as limited time and the need for experienced supervisors and strategies to address these issues were identified. Overall, the research underscores the vital role of effective academic supervision in fostering teacher professionalism and enhancing educational quality, suggesting that these practices could be adopted in other educational settings to achieve similar benefits.